(untitled) (Al-Academy, 2021)
The dramatic personality represents the most important nerve in the cinematographic discourse due to what it represents of a permanent presence in various types of TV and cinematic stories. That is what makes the cinematographic discourse always seek to introduce the human personality in multiple methods. The psychopathic personality is a type of the personalities that got distinguished presence in the TV and cinematic productions. This is what drew the researcher’s attention for the topic of the research for which she used title: structural features of the psychopathic personality in the cinematographic discourse. The theoretical framework included the research problem which is determined by the following question: what are the structural features of the psychopathic personality in the cinematographic discourse? The researcher, then, determined the importance of the research as well as the research objective and limits. The theoretical framework consists of two sections: the first section: the psychopathic personality, features and types. The second section: the cinematographic structure of the psychopathic personality. The researcher concluded a number of indicators from the theoretical framework. The research procedures included the research methodology, tool, community, analysis unit, and sample. Finally the analysis of the intentional sample represented by the cinema movie (Split). The researcher came up with a set of results from the analysis of the research sample and conclusions